Augusto Salazar Bondy: North-American capitalism as antithesis to the republican ideals of the Perú in the 19th century - Gonzáles Auccasi, Jorge Rolando (2023)
The objective of the investigation that we propose to carry out is to contrast what the Republic of Perú turned out to be, one hundred and thirty years after its independence, with the establishment of the capitalism in Perú in the 20th century, seen from the perspective of the peruvian philosopher Augusto Salazar Bondy in his book Between Scylla and Charybdis; according to his analysis, it was a system that only brought domination and economic dependence to our country, further accentuating the separation between peruvians and perpetuating the submission of our nation to the dictates and interest of the United States of America, an aspect for which we think was the antithesis to the republican ideals, since it was in direct contradiction to the postulates of the ideologues of the independence of Perú, José Faustino Sánchez Carrión and Manuel Lorenzo de Vidaurre, when they opted for the republic as a system of government in the 19th century.